Entrepreneurs-politiciens : défi ou dérive d’un nouveau genre d’hommes d’affaires en Haïti ? - Bénédique Paul (Études Caribéennes)
In 2015, several Haitian entrepreneurs invested the political arena and wanted to be elected at different levels (mayors, members of Parliament, and president). Does this new turn the emergence of a new kind of business men or their conversion into more voracious rent-seekers, in the sense of Fritz A. Jean? For a long time, economic and political elites were two isolated entities in Haiti. It was not common that entrepreneurs, most of the successful one are immigrants, were visibly active in politics. With the expansion of entrepreneurial context, a new trend seems to be initiated, because of the apparition of many new entrepreneurs from the middle and the lower class, during the last two decades. We analyze the case of the entrepreneurs who have run for election in the 2015-2016 political polls. We adopted a mixed approach mobilizing institutionalism and behavioral dynamic in entrepreneurship. We conclude that those candidates, instead to become entrepreneurs-in-politics, they fail to become entrepreneurs who maximize collective profit and are transformed into what we call « rent-seekers of the Republic ». But, taking into account the reduction of the State’s available resources and other depredation possibilities, we argue that the decision of this new kind of entrepreneur is effective neither from the individual point of view nor from the collective perspective.